Protocolo para la prevención de neumonía asociada a la ventilación mecánica en el departamento de neumología - Moyón Granda, Carlos Alfonso (2025)
Background: Prolonged use of mechanical ventilation in pulmonary patients is an essential intervention but also at the same time, it increases the risk of complications such as ventilator-associated pneumonia. Objective: To identify protocols for the prevention of ventilator-associated pneumonia in the pulmonology department. Methodology: A non-experimental, descriptive bibliographic review was conducted using the PRISMA selection method. Clinical practice guidelines and scientific articles were available from databases like Dialnet, PubMed, Scielo, and Science Direct. The information was searched using Boolean operators and terms extracted from health sciences descriptors (DeCS): "Pneumology," "Asthma," and "Treatment." Results: The profound bibliographic review of the main preventive strategies for ventilator-associated pneumonia (VAP) and the evaluation of their clinical practice impact identified the need for a more personalized approach to optimize the care of patients on mechanical ventilation, particularly in the pulmonology department. Conclusions: Based on the obtained results, a personalized prevention protocol for ventilator-associated pneumonia was developed, which can significantly improve the clinical outcomes of critical patients with chronic respiratory diseases.